Advanced Malignant Melanoma of the Vulva in a 70 years old woman - ABUYE, BINYAM ESAYAS (Ethiopian Journal of Reproductive Health, 2024)
Vulvar melanoma is a rare malignant tumor of the female genital tract tend to occur in older age women and a high tendency to metastasize because the diagnosis is usually delayed (1). In this case report, we present a 70-year-old para 8 woman who presented with progressively increasing vulvar swelling of 2 years and multiple visit to health institution. Examination revealed 7cm diameter multi-nodular mass with areas of dark and dark blue-violet color filling the introitus that involves the clitoris, labia minora, lower third of the anterior vagina and urethra. Incisional biopsy from the mass showed malignant melanoma. Imaging with CT scan revealed bilateral lung metastasis. Palliative chemotherapy was planned but the patient lost to follow up.